The Indirect Impact of Profitability on Firm Value: Evidence Dividend Policy as Moderators and Capital Structure as Mediator - Achmad Budi Susetyo; Agus Eko Sujianto; Mochamad Arif Faizin; Kiki Yunita Anjarsari; Charina Dwi Rivylina Nafisah (Technium Social Sciences Journal, 2020)
Firm value is a basis for investors in deciding whether or not to invest in a firm. Therefore, a study on issuer’s strategies to maximize firm value requires special attention, especially in dealing with the Islamic capital market which is growing rapidly from time to time. A particular study is important to be conducted to look at the factors that have a direct or indirect effect on a firm’s value, which includes; profitability, capital structure, and dividend policy. The path analysis approach is employed in the current study to reveal the effect of profitability on firm value, both directly and indirectly, with the intermediaries of capital structure and dividend policy. The results of the analysis indicate that profitability has a direct positive and significant effect on firm value and a negative and significant effect on capital structure, while the capital structure has a negative and insignificant effect on firm value. Indirectly, dividend policy moderates and strengthens the effect of profitability on firm value, but on the other hand, the capital structure does not mediate the effect of profitability on firm value. The absence of capital structure role in mediating the relationship between profitability and the firm value indicates that investors can determine the value of the firm directly by simply looking at the level of profitability, regardless of management’s strategy in arranging the capital structure.